2015
DOI: 10.1073/pnas.1416276112
|View full text |Cite
|
Sign up to set email alerts
|

Functional capacities of human IgM memory B cells in early inflammatory responses and secondary germinal center reactions

Abstract: The generation and functions of human peripheral blood (PB) IgM CD27+ B cells to migrate to B-cell follicles and undergo germinal center (GC) B-cell differentiation, whereas activated IgG + memory B cells preferentially showed a plasma cell (PC) fate. This observation was supported by reverse regulation of B-cell lymphoma 6 and PR domain containing 1 and differential BTB and CNC homology 1, basic leucine zipper transcription factor 2 expression. Moreover, IgM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
204
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(228 citation statements)
references
References 74 publications
21
204
2
1
Order By: Relevance
“…We have previously shown that, in contrast to vaccination with PCV13, which resulted in an increase of levels of antigen-specific memory B cells (MBCs), in splenectomized subjects with ␤-thalassemia, a history of previous vaccinations with PPV23 had an attenuating effect on antigen-specific MBC pool levels (60). Our findings are in accordance with recent data from studies in murine models as well as in human lymphocytes which have shown that, upon secondary challenge with a T-independent antigen, such as the anti- (71)(72)(73). The proposed mechanisms for the effect of PPV23 on the antigen-specific memory B-cell pool and in relation to previous or subsequent vaccination with a pneumococcal conjugate vaccine are illustrated in Fig.…”
Section: Immunological Hyporesponsivenesssupporting
confidence: 92%
“…We have previously shown that, in contrast to vaccination with PCV13, which resulted in an increase of levels of antigen-specific memory B cells (MBCs), in splenectomized subjects with ␤-thalassemia, a history of previous vaccinations with PPV23 had an attenuating effect on antigen-specific MBC pool levels (60). Our findings are in accordance with recent data from studies in murine models as well as in human lymphocytes which have shown that, upon secondary challenge with a T-independent antigen, such as the anti- (71)(72)(73). The proposed mechanisms for the effect of PPV23 on the antigen-specific memory B-cell pool and in relation to previous or subsequent vaccination with a pneumococcal conjugate vaccine are illustrated in Fig.…”
Section: Immunological Hyporesponsivenesssupporting
confidence: 92%
“…Our data is in line with previous reports showing deficiency in CD27+IgD+ cells in SLE [18,19], though in contrast to earlier study [18], we did not see any association of B-cell NSM percentage with disease activity status. The subset of NSM B-cells has been implicated in immune responses against T-cell independent antigens, however recent studies confirmed their role as a long-lasting memory to T-cell dependent antigens involved in reconstitution of switched memory pool upon antigen restimulation [10]. Changes in NSM fraction were accompanied by increased percentage of immature/ /early-transitional B-cells and activated SM cells, both [8,16,23].…”
Section: Discussionmentioning
confidence: 97%
“…But autoreactive B-cells are only a tiny fraction of all memory cells, so why the whole compartment is changed? Some hints came from recent study, showing that various neutrophil-derived proinflammatory mediators facilitate differentiation of IgD+ CD27+ memory B-cells and IgG class switch [10]. Neutrophils participate in the pathogenesis of LN, and both neutrophil derived cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, murine and also human IgM memory B cells preferentially reenter GC reactions (37,42), although also IgG memory B cells have this capacity (43). Some clones are characterized by many individual mutations per clone member (Fig.…”
Section: Cd27mentioning
confidence: 98%